Physical and Chemical Quality of Fresh Maggots Cultivated with Special Application of The Media Used - Dwi Kusuma Purnamasari; Erwan; Sumiati; Rijki Purnama S (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The high price of protein feed for livestock makes maggots potential as an alternative protein feed. The first stage in this research was maggot maintenance and maggot harvesting on the 15th day of maintenance. Next, measurements of the physical and chemical quality of fresh maggot were carried out. Parameters for measuring the physical quality of fresh maggot consist of harvest weight, individual weight, individual length and color. The parameters for measuring the chemical quality of fresh maggot consist of water content, ash, crude fat, crude fiber and crude protein. Data analysis was carried out using the Independent Sample T-test. The results showed that the maggot that was cultivated with the special media used had an average harvest weight of 1.24 kg, while the maggot that was cultivated without the special media used had an average harvest weight of 0.72 kg. The maggot that was cultivated with the special treatment of the media used contained 31.5% protein, while the maggot that was cultivated without the special treatment of the media used contained 32.9% protein. The conclusion of this study is that maggot that is cultivated with the special treatment of the media used produces maggot with superior physical quality compared to maggot that is cultivated without the special treatment of the media used.